Medicinal Plant Diversity and Inter-Cultural Interactions between Indigenous Guarani, Criollos and Polish Migrants in the Subtropics of Argentina - Kujawska, Monika (2017)
Numerous studies highlight the importance of phytotherapy for indigenous and non-indigenous people in different parts of the world. In this work we analyze the richness (number of species), diversity (plant identity and the number of illnesses for which it is used) and similarity of plant species and illnesses treated with them, in order to contribute new data and insight into the importance of plant medicines to the local medical systems of people living in Misiones province, in the subtropics of Argentina. Three sympatric groups were compared: Guarani Indians, Criollos (mestizos) and Polish migrants. Quantitative scrutiny was focused on both primary and secondary sources. The similarity and diversity of medicinal plants and uses between groups was calculated by applying the Sørensen quantitative coefficient and the Shannon-Wiener index, respectively. In order to identify the characteristic plant species used by each group, the Cultural Importance and Prevalence Value (CIPV) was calculated based on the species Indicator Value (IndVal), which combines a species relative abundance with its relative frequency of occurrence in the various groups, and modified according to the type of the analyzed data. The important finding is a great variation in the number of species used by the study groups. Altogether, 509 botanical species were registered: Guarani (397), Criollos (243) and Polish migrants (137). For all groups, the use of native medicinal plants prevailed. The Guarani appear to be the local experts in use of medicinal plants. There is the significant difference in the number of treated illnesses by each taxon among three groups. Criollos and Polish migrants exhibit the greatest similarity in illnesses treated with medicinal plants. These groups share a corpus of knowledge related to illness nosology, and have a symptomatic approach to illness treatment. The Guarani have an etiological approach to illness diagnosis and healing, which may be viewed as a barrier to the exchange of knowledge about home medicine with other ethnic groups of Misiones